2010
DOI: 10.1007/s11325-010-0391-y
|View full text |Cite
|
Sign up to set email alerts
|

Factors that influence CPAP adherence: an overview

Abstract: These factors are reviewed and pragmatic recommendations are made for improving clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
98
1
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(107 citation statements)
references
References 81 publications
3
98
1
5
Order By: Relevance
“…Hawkins, MD 1,2 ; Emily L. Jensen, BS 3,4 may result in development of the aforementioned comorbidities, compromised daily functioning, increased health care utilization, and contribution to early mortality. 6,[15][16][17][18][19][20][21][22][23] OSA severity, pressure settings, and mask type, have not been found to affect use, 14,[24][25][26][27][28][29][30] whereas psychosocial factors and perception of OSA's importance do. 14,23,31 One study suggested that higher maternal education correlated with higher adherence.…”
Section: Correlates Of Pediatric Cpap Adherencementioning
confidence: 99%
“…Hawkins, MD 1,2 ; Emily L. Jensen, BS 3,4 may result in development of the aforementioned comorbidities, compromised daily functioning, increased health care utilization, and contribution to early mortality. 6,[15][16][17][18][19][20][21][22][23] OSA severity, pressure settings, and mask type, have not been found to affect use, 14,[24][25][26][27][28][29][30] whereas psychosocial factors and perception of OSA's importance do. 14,23,31 One study suggested that higher maternal education correlated with higher adherence.…”
Section: Correlates Of Pediatric Cpap Adherencementioning
confidence: 99%
“…16 Oxygen administration has been used as an alternative treatment in patients with OSA who are not somnolent or not compliant with CPAP; the purpose of supplemental oxygen in this situation is to reduce the deleterious effects of transient hypoxemia during sleep. 17 Supplemental oxygen has been shown to be effective in improving the AHI, respiratory arousal index, and nocturnal desaturation during apneic episodes.…”
mentioning
confidence: 99%
“…15 Common side effects related to CPAP use include pressure intolerance, dryness of nasal and pharyngeal membranes, nasal symptoms, and eye irritation. 16 Recent advancements in mask designs provide better mask fit and more selections to the patients that may provide more positive CPAP experiences and increased compliance. There are concerns in the field that use of nasal pillows at higher CPAP pressure may lead to more CPAP related side effects such as nasal symptoms and jetting.…”
Section: Discussionmentioning
confidence: 99%